Ultra-high-resolution assessment of lesion extension after cryoballoon ablation for pulmonary vein isolation - Spera, Francesco; Narducci, Maria Lucia; Bencardino, Gianluigi; Perna, Francesco; Bisignani, Antonio; Pinnacchio, Gaetano; Tondo, Claudio; Maggio, Ruggero; Stabile, Giuseppe; Iacopino, Saverio; Tundo, Fabrizio; Ferraro, Anna; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction. Unrecognized incomplete pulmonary vein (PV) isolation during the index procedure, can be a major cause of clinical recurrences of atrial fibrillation (AF) after cryoballoon (CB) ablation. We aimed to characterize the extension of the lesions produced by CB ablation and to assess the value of using an ultra-high resolution electroanatomic mapping (UHDM) system to detect incomplete CB lesions. Methods. Twenty-nine consecutive patients from the CHARISMA registry undergoing AF ablation at 4 Italian centers were prospectively evaluated. The RhythmiaTM mapping system and the OrionTM (Boston Scientific) mapping catheter were used to systematically map the left atrium and PVs before and after cryoablation. Results. A total of 116 PVs were targeted and isolated. Quantitative assessment of the lesions revealed a significant reduction of the antral surface area of the PV, resulting in an ablated area of 5.7±0.7cm2 and 5.1±0.8cm2 for the left PV pair and right PV pair, respectively (p=0.0068). The mean posterior wall (PW) area was 22.9±2cm2 and, following PV isolation, 44.8±6% of the PW area was ablated. After CB ablation, complete isolation of each PV was documented by the POLARMapTM catheter in all patients. By contrast, confirmatory UHDM and the LumipointTM tool unveiled PV signals in 1 out of 114 of the PVs (0.9%). Over 30-day follow-up, no major procedure-related adverse events were reported. After a mean follow-up of 333days, 89.7% of patients were free from arrhythmia recurrence. Conclusions. The lesion extension achieved by the new CB ablation system involved the PV antrum, with less than 50% of the PW remaining untouched. The new system, with short tip and circular mapping catheter,failed to achieve PV isolation in only 0.9% of all PVs treated.